Evaluation of Outcomes in Patients With Carcinoma of the Cervix Treated With Concurrent Radiation and Cisplatin Versus Cisplatin/5-FU Compared With Radiation Alone. (October 2015) - Donnelly, Eric D.; Refaat, Tamer; Gentile, Michelle; Herskovic, Alex; Boyle, John; Helenowski, Irene; Rademaker, Alfred; Lurain, John; Schink, Julian; Singh, Diljeet; Strauss, Jonathan B.; Small, William
<x xml:space="preserve">Abstract</x> Objectives: The objective of this study was to compare outcomes for patients with cervical cancer treated with radiation concurrently with cisplatin, cisplatin/5-fluorouracil (5-FU), or without chemotherapy. Materials and Methods: We reviewed the records of eligible patients with locoregionally confined, stage IB1 through IVA, intact cervical cancer who were treated at Northwestern Memorial Hospital. All patients underwent definitive radiotherapy with combined external beam radiation—the majority with extended-field (62%)—and received low-dose rate brachytherapy. Results: A total of 236 patients were included: 99 had no concurrent chemotherapy, 95 were treated with concurrent cisplatin, and 42 were treated with cisplatin/5-FU. For all patients treated with or without chemotherapy, overall survival at 5 and 10 years was 64% and 59%, respectively. Patients treated with chemotherapy had a superior recurrence-free survival rate of 69% at 5 years versus 49% in patients who did not receive chemotherapy (P=0.09). Twenty-six percent of patients treated with cisplatin alone, 31% of patients treated with cisplatin/5-FU, and 45% of patients who did not receive chemotherapy experienced a disease recurrence. Adenosquamous histology conferred a higher rate of recurrence as compared with adenocarcinoma and squamous cell histologies (54% vs. 34%, respectively; P=0.05). Conclusions: Cisplatin-based concurrent chemoradiotherapy showed a trend toward improved recurrence-free survival survival in the definitive treatment of nonmetastatic cervical cancer. The addition of 5-FU to cisplatin did not appear to significantly impact survival or recurrence-free survival. Adenosquamous histology was associated with a higher risk of recurrence as compared with other histologic subtypes.